ETHNIC GROUPS, DEVELOPMENT AND - ' CURRENT SITUATION IN NUNUKAN - John Haba (Jurnal Kependudukan Indonesia, 2006)
In 2002, Nunukan was authoritative as new regency in East Kalimantan. The role of this new regency become more important for its function as a "transit zone" to Tawau (Sabah) and Nunukan is also used as a transit place for TKI (Indonesian Labor Force) that being deported from Malaysia in 2002. Other problems that may occur in border areas are human smuggling and commodities smuggling. For Nunukan, the major difficulty in handling the TKI deportation was this regency has no sufficient infrastructure to cope the amount of TKI. The increase of its migrant population puts more burdens on the local government. The present migrants from of various ethnic groups were set enviousness that causes a striking domination in economic sector and social lives. These kinds of homogeneity which related to ethnicity, resources and occupation may create negative effects to the Nunukan 's development.